The Solvency, Firm Size, and The Timeliness of Financial Reporting: Evidence From Energy Sector Companies - Rizkia Chudri, Intan; Elviza; Aida Fitri; Nara Pristiwa; Maidar (Jurnal Reviu Akuntansi dan Keuangan, 2026)
Purpose: This study aims to examine the effect of solvency and company size on the timeliness of financial reporting, both simultaneously and partially, in energy sector companies. Methodology/Approach: This research employs a quantitative approach using multiple linear regression analysis. The sample consists of 87 energy sector companies listed on the Indonesia Stock Exchange during the 2023–2024 period. The study uses secondary data derived from published annual financial reports. Findings: The results indicate that solvency and company size simultaneously influence the timeliness of financial reporting. Partially, solvency has a negative effect on reporting timeliness, suggesting that companies with higher leverage levels tend to delay financial reporting. Conversely, company size has a positive effect, indicating that larger companies are more likely to report their financial statements in a timely manner. Practical Implications: The findings provide insights for investors, regulators, and company management regarding the importance of maintaining healthy financial structures and adequate organizational resources to ensure timely financial reporting. Originality/Value: This study contributes updated empirical evidence on the determinants of financial reporting timeliness within the energy sector context, particularly during the 2023–2024 period. It enriches the literature by examining solvency and company size as key financial characteristics influencing reporting discipline.